Reduction of Salmonella contamination on the surface of chicken skin using bacteriophage - Atterbury, Robert Joseph (Virol J, 2020)
BACKGROUND: Enteric infections caused by Salmonella spp. remain a major public health burden worldwide. Chickens are known to be a major reservoir for this zoonotic pathogen. The presence of Salmonella in poultry farms and abattoirs is associated with financial costs of treatment and a serious risk to human health. The use of bacteriophages as a biocontrol is one possible intervention by which Salmonella colonization of chickens could be reduced. In a prior study, phages Eϕ151 and Tϕ7 significantly reduced broiler chicken caecal colonization by S. Enteritidis and S. Typhimurium respectively. METHODS: Salmonella-free Ross broiler chickens were orally infected with S. Enteritidis P125109 or S. Typhimurium 4/74. After 7 days of infection, the animals were euthanased, and 25cm(2) sections of skin were collected. The skin samples were sprayed with a phage suspension of either Eϕ151 (S. Enteritidis), Tϕ7 phage suspension (S. Typhimurium) or SM buffer (Control). After incubation, the number of surviving Salmonellas was determined by direct plating and Most Probable Number (MPN). To determine the rate of reduction of Salmonella numbers on the skin surface, a bioluminescent S. Typhimurium DT104 strain was cultured, spread on sections of chicken breast skin, and after spraying with a Tϕ11 phage suspension, skin samples were monitored using photon counting for up to 24 h. RESULTS: The median levels of Salmonella reduction following phage treatment were 1.38 log(10) MPN (Enteritidis) and 1.83 log(10) MPN (Typhimurium) per skin section. Treatment reductions were significant when compared with Salmonella recovery from control skin sections treated with buffer (p < 0.0001). Additionally, significant reduction in light intensity was observed within 1 min of phage Tϕ11 spraying onto the skin contaminated with a bioluminescent Salmonella recombinant strain, compared with buffer-treated controls (p < 0.01), implying that some lysis of Salmonella was occurring on the skin surface. CONCLUSIONS: The results of this study suggest that phages may be used on the surface of chicken skin as biocontrol agents against Salmonella infected broiler chicken carcasses. The rate of bioluminescence reduction shown by the recombinant Salmonella strain used supported the hypothesis that at least some of the reduction observed was due to lysis occurred on the skin surface.